Desain Community Center Desa Mekarwangi Kabupaten Tangerang Provinsi Banten - Khamdevi, Muhammar; Effendi, Andrey Caesar (LPPM Universitas Flores, 2023)
Mekarwangi Village does not yet have adequate public space. Meanwhile Mekarwangi Village is growing rapidly because of the growth of formal housing in the Cisauk area, so it is necessary to build a public space immediately before the village's land runs out. There is a village-owned land of 2000 square meters which is an opportunity to work on. So, on this land a community center will be planned to be designed that can accommodate the needs of public space and educational space for residents as well as the need for space for the village government with various uses for. The results of this community cervice are in the form of analysis documents, concepts and working drawings, with an approach that considers local potential and character.